2015
DOI: 10.1002/2014jc010067
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of spaceborne sea surface salinity observations over the northern North Atlantic

Abstract: SMOS SSS fields show a temperature-dependent negative SSS bias of up to 22 g/kg for temperatures <5 C. Removing this bias significantly reduces the differences to independent ship-based thermosalinograph data but potentially corrects simultaneously also other effects not related to temperature, such as land contamination or radio frequency interference (RFI). The resulting time-mean bias, averaged over the study area, amounts to 0.1 g/kg. A respective correction applied previously by the Jet Propulsion Laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 43 publications
0
46
0
Order By: Relevance
“…In contrast, Köhler et al . [] investigated the quality of SMOS and Aquarius data over cold water in the North Atlantic to assess their data quality under a worst case scenario.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Köhler et al . [] investigated the quality of SMOS and Aquarius data over cold water in the North Atlantic to assess their data quality under a worst case scenario.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies (e.g., Banks et al, ; Köhler et al, ; Tong et al, ) showed that satellite‐retrieved SSS is corrupted by systematic errors coming from ice and land contamination (Font et al, ; Gabarro et al, ; Oliva et al, ), radio frequency interference (RFI; Oliva et al, ), seasonal biases, or latitudinal biases mainly due to thermal drift of the instrument (e.g., Boutin et al, ; Gourrion et al, ; Reul et al, ). Those biases are difficult to characterize and several institutions provide satellite‐retrieved SSS products based on different correction methods (e.g., Kolodziejczyk et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The recently available SMOS (Soil Moisture and Ocean Salinity) satellite [25,26] provides sea surface salinity data with sufficient spatial resolution (1/4 • ) to characterize global [27] and regional (e.g., Amazon: [28]; North Atlantic SSS maximum: [29,30]; Gulf Stream: [31]; northern North Atlantic: [32]) features. Recently, SMOS data have been used to study salinity variability in the Atlantic [33], the signature of La Niña in the tropical Pacific Ocean [34] and even create surface temperature/salinity (T/S) diagrams [35].…”
Section: Smos Satellite Datamentioning
confidence: 99%
“…The SMOS satellite data exhibited deficiencies near coastal areas and in high latitudes [29,32,37,38]. To prevent the introduction of bogus features, those data were removed from the analysis.…”
Section: Smos Satellite Datamentioning
confidence: 99%